¿Responsabilidad estructural versus responsabilidad por el hecho? Filosofía y responsabilidad penal de las personas jurídicas - Feijoo Sánchez, Bernardo (2025)
The text reflects, with the aim of complementing previous contributions, on the ultimate basis of the criminal liability of legal persons, an issue that has gone from being marginal to occupying a central place in the debate on the dogmatics of criminal law. The debate focuses on philosophical and dogmatic aspects, highlighting Professor Juan Pablo Mañalich Raffo’s proposal of “culpability by character”, which attributes criminal liability to legal persons based on their “nature”. It sets out the agreement, but also the disagreement, with this innovative proposal, in particular because the emphasis on the structural defects of organisations as a basis for liability would imply a detachment from concrete facts. The text argues that in order to address the complexity of corporate liability, structural elements should be combined with specific facts as the object of imputation, advocating a model that links criminality to organisational characteristics and not just to corporate culture or character. This view highlights the implementation of criminal compliance management systems as an exclusion from corporate liability understood as structural liability.